Immutable Ubiquitous Digital Certificate Authentication Using Blockchain Protocol - Rahardja, Untung; Hidayanto, Achmad Nizar; Putra, Panca Oktavia Hadi; Hardini, Marviola (Journal of Applied Research and Technology, 2021)
A new paradigm regarding a significant technological development has been introduced, each individual gets full trust in controlling an asset and can see the level of authenticity of a particular asset. Through qualitative methods, it is possible to have structured results as the first step to the perfection of the digitalisation era, in which the current revolutionary technology called blockchain has come into play. One of the main innovations found through this research is the role of blockchain in enhancing e-certificate data security, it is proven that administration can be well distributed and reduce operational costs for every field in the world. It is clear that blockchain, especially in the world of education certification, has a big impact, because it can create a global trust network, immutable, authenticated ubiquitous, and can shape a better world for Indonesia as a superpower. With good execution using the SHA-256 hash, e-certificate blockchain technology can be of high value and have an impact on the quality of potential human resources in educational institutions.